Modulating Supramolecular Charge‐Transfer Interactions in the Solid State using Compressible Macrocyclic Hosts - Wu, Jia‐Rui; Li, Dongxia; Wu, Gengxin; Li, Meng‐Hao; Yang, Ying‐Wei (Angewandte Chemie International Edition, 2022)
Modulating intermolecular charge‐transfer (ICT) interactions between specific donor and acceptor species in host–guest systems is a big challenge and full of research value in supramolecular chemistry and materials science. In this work, a strategy to modulate the supramolecular ICT interactions in the solid state is developed by compressing the binding cavity of a macrocyclic host named perethylated leaning pillar[6]arene (p‐EtLP6). The solid‐state ICT affinities of p‐EtLP6 toward multi‐types of electron‐deficient planar guests could be significantly enhanced by transforming the macrocyclic backbone from the original para‐bridged mode into a hybrid para‐ and meta‐bridged isomeric form (m‐EtLP6). X‐ray single‐crystal structural analyses incorporating theoretical calculation demonstrate that the improved ICT affinities are mainly attributed to the superior host–guest size fit arising from the compressed binding cavity in m‐EtLP6 as compared with p‐EtLP6. A cavity compressing strategy is proposed to modulate the macrocyclic host–guest charge‐transfer (CT) interactions. The solid‐state CT affinities of perethylated leaning pillar[6]arene toward various electron‐deficient planar guests could be significantly enhanced by transforming the macrocyclic backbone from the original para‐bridged mode into a hybrid para‐ and meta‐bridged isomeric form.